GRI Standard Implementation on Sustainability Report of Indonesia Sustainability Reporting Award (ISRA) Winners - Fandy Cahya Krishnanda; Unti Ludigdo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This descriptive qualitative study aims for analyzing the performance and focus of CSR at two most consistent participants of Indonesia Sustainability Reporting Award (ISRA), which are PT. Kaltim Prima Coal (KPC) and PT. Aneka Tambang, Tbk (ANTAM), from 2010 up to 2013. The data are collected through documentation and literature review techniques and evaluated by descriptive analysis upon the sustainability report of 2009 until 2013 with GRI standard as its indicator. This research confirms that the main focus of GRI standard is Social Performance Indicator. It is apparent that GRI always develops all indicators except the Economic Performance Indicator. Comparing the sustainability reports, the study revealed that the performance of KPC in the annual ISRA increased gradually from 2010 until 2014 and was more stable than that of ANTAM. The result of analysis upon the sustainability report of 2011 until 2013 with GRI G3.1 showed that the CSR main focus of KPC was toward the Economic and Social Performance Indicators with 100% of indicator fulfillment; meanwhile, the CSR main focus of ANTAM was on the Environmental Performance Indicator with 95.6% of indicator fulfillment. Key words: GRI, ISRA, sustainability report, PT Kaltim Prima Coal, PT Aneka Tambang Tbk